2017
DOI: 10.1016/j.sbi.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Protein structural motifs in prediction and design

Abstract: The Protein Data Bank (PDB) has been an integral resource for shaping our fundamental understanding of protein structure and for the advancement of such applications as protein design and structure prediction. Over the years, information from the PDB has been used to generate models ranging from specific structural mechanisms to general statistical potentials. With accumulating structural data, it has become possible to mine for more complete and complex structural observations, deducing more accurate generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 60 publications
(88 reference statements)
0
27
0
Order By: Relevance
“…Recent methodological developments have shown that mining sequence-structure relationships from the PDB has the potential to improve the efficiency and efficacy of structure-based modeling and design (Debartolo et al, 2012;DeBartolo et al, 2014;Feng and Barth, 2016;Fernandez-Fuentes et al, 2006;Mackenzie and Grigoryan, 2017). It has long been recognized that proteins are composed of recurring structural elements (Jacobs et al, 2016;Vanhee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent methodological developments have shown that mining sequence-structure relationships from the PDB has the potential to improve the efficiency and efficacy of structure-based modeling and design (Debartolo et al, 2012;DeBartolo et al, 2014;Feng and Barth, 2016;Fernandez-Fuentes et al, 2006;Mackenzie and Grigoryan, 2017). It has long been recognized that proteins are composed of recurring structural elements (Jacobs et al, 2016;Vanhee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By harnessing the power of computers, thousands of designs can be generated and analysed in silico at scales beyond minimal and rational design. The most widespread approach is fragmentbased design, which has three aspects: libraries of fragments or motifs are taken from structural databases, algorithms are developed to combine these to assemble target structures, and scoring functions are used to assess both the assembled structures and sequences that best fit onto them (Figure 1) [69][70][71][72]. This is epitomised by the Rosetta suite for computational protein design developed by the Baker group [73].…”
Section: Fragment-based Computational Design Beyond Protein Engineeringmentioning
confidence: 99%
“…The sequence search can be limited strictly by only considering the amino acids observed at that position in homologs of the template sequence [96], or exclude conserved residues entirely and focus on optimization of the areas of the protein that are less conserved. Structural motifs that have been found to be stable [97] in wide variety of contexts may also be used. Alternatively, co-evolving residue pairs outside the main interacting surface may be an indication that long-range electrostatics are important and the scope of the design should be expanded [98].…”
Section: Challenges In Automated Protein Designmentioning
confidence: 99%
“…Almost every scoring function used in popular protein design algorithm, such as those used in RosettaDesign [128,153,171], FoldX [122], or OSPREY [106], falls into this category. Evodesign uses a combination of knowledge-based scores based in amino acid frequency at the corresponding location within structural related protein, machine-learning-based prediction of secondary and tertiary structure, and the physics-based FoldX force field [97,150]. …”
Section: Challenges In Automated Protein Designmentioning
confidence: 99%